Dictionaries: A Very Short Introduction - Mugglestone, Lynda (New York Oxford University Press, 2011)
Dictionaries are far more than works which list the words and meanings of a language. In this Very Short Introduction Lynda Mugglestone takes a look at how dictionaries are made, considering how they reflect the dominant social and cultural assumptions of the time in which they were written.
Includes Index and Illustrations.
Keywords: Encyclopedias and dictionaries